2017
DOI: 10.1002/1873-3468.12739
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic and solution structure of the N‐terminal domain of the Rel protein from Mycobacterium tuberculosis

Abstract: Modulation of intracellular guanosine 3′,5′‐bispyrophosphate ((p)ppGpp) level, the effector of the stringent response, is crucial for survival as well as optimal growth of prokaryotes and, thus, for bacterial pathogenesis and dormancy. In Mycobacterium tuberculosis (Mtb), (p)ppGpp synthesis and degradation are carried out by the bifunctional enzyme MtRel, which consists of 738 residues, including an N‐terminal hydrolase‐ and synthetase‐domain (N‐terminal domain or NTD) and a C‐terminus with a ribosome‐binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 47 publications
(80 reference statements)
2
53
1
Order By: Relevance
“…Our previous results (Gropp et al, 2001) showed the importance of the last two domains (AA 564-744), and the importance of the three Cys residues present in the RIS domain (Loveland et al, 2016; Figure 1A), especially in protein-protein interactions. This was also reinforced with recent reports about the involvement of the CTD in the oligomerization of Rel protein in Mycobacterium (Singal et al, 2017) and also in the regulation of Bacillus Subtilis Rel synthetic activity (Pausch et al, 2020). Here, we closely examined RelA-RelA via its CTD interactions in vitro by using purified ribosomes (70S) where lack of charged tRNA in the tube mimic amino acid stress conditions.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Our previous results (Gropp et al, 2001) showed the importance of the last two domains (AA 564-744), and the importance of the three Cys residues present in the RIS domain (Loveland et al, 2016; Figure 1A), especially in protein-protein interactions. This was also reinforced with recent reports about the involvement of the CTD in the oligomerization of Rel protein in Mycobacterium (Singal et al, 2017) and also in the regulation of Bacillus Subtilis Rel synthetic activity (Pausch et al, 2020). Here, we closely examined RelA-RelA via its CTD interactions in vitro by using purified ribosomes (70S) where lack of charged tRNA in the tube mimic amino acid stress conditions.…”
Section: Discussionmentioning
confidence: 73%
“…To survive, bacteria must be able to respond to changes in their environment. Depriving Escherichia coli of one or more amino acids (AAs) triggers the stringent response (Stent and Brenner, 1961;Cashel, 1969;Cashel and Gallant, 1969;Kaspy et al, 2013). Within a few seconds after the onset of amino-acid starvation, one can observe the accumulation of phosphorylated derivatives of GTP and GDP, collectively called (p)ppGpp (Cashel, 1969;Cashel and Gallant, 1969;Fiil et al, 1972;Lund and Kjeldgaard, 1972).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, our data show that SpoT harbours at least two multimerization domains, (i) ACT at the C-terminal end and (ii) another one located in the N-terminal catalytic domains (Figure 1 and our unpublished data). Note that the N-terminal extremity of M. tuberculosis Rel harbouring the catalytic domains was already shown to homo-dimerize (31). In addition, the ACT alone can interact with full length SpoT but not with SpoT ΔACT (Figure 1 and Supplementary Figure S1), showing that the ACT domain unlikely interferes directly with HD.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, this was impossible to do with the RelA/RSH (RelA-SpoT homolog) family of enzymes, as there were no adequate high-resolution molecular structures available. However, several RelA and related enzyme structures have been recently characterized and published: RelA ( E. coli ) [ 36 ], RelP ( Staphylococcus aureus ) [ 37 ], RelQ ( S. aureus ) [ 38 ], Rel seq ( Streptococcus equisimilis ) [ 39 ], and Rel ( Mycobacterium tuberculosis ) [ 40 ]. Thus, it has become possible through alignment and homology studies to determine the active residues within the catalytic center of these enzymes and to specifically target this region to predict and understand the ligand binding events for the rational identification of inhibitors.…”
Section: Introductionmentioning
confidence: 99%